The effect of interventions to reduce fertility on economic growth - Quamrul H. Ashraf; David N. Weil; Joshua Wilde (Brown University, Department of Economics, 2011)
We assess quantitatively the effect of exogenous reductions in fertility on output per capita. Our simulation model allows for effects that run through schooling, the size and age structure of the population, capital accumulation, parental time input into child-rearing, and crowding of fixed natural resources. The model is parameterized using a combination of microeconomic estimates, data on demographics and natural resource income in developing countries, and standard components of quantitative macroeconomic theory. We apply the model to examine the effect of an intervention that immediately reduces TFR by 1.0, using current Nigerian vital rates as a baseline. For a base case set of parameters, we find that an immediate decline in the TFR of 1.0 will raise output per capita by approximately 13.2 percent at a horizon of 20 years, and by 25.4 percent at a horizon of 50 years.
Additional information: NBER Working Paper No. 17377.
Keywords: E17; J11; J13; J18; O11; 330; Bevölkerungsentwicklung; Familienplanung; Öffentliche Bildungsausgaben; Ressourcenökonomik; Wirtschaftswachstum; Prognose; Theorie; Nigeria